Laboratory tests based strength evaluation of alluvial soil: A case study - Hoque, Md. Ikramul; Hasan, Muzamir; Hossain Khondoker, Md. Tareq (HBRP Publication, 2023)
This article represents an analysis of alluvial soil behaviour using laboratory tests where samples being collected from different parts of Khulna, Bangladesh. Bangladesh is a riverine country and 80% of soil in Bangladesh is alluvial. Especially, the Khulna region stands on the Gangetic alluvial soil track that poses a challenge to the foundation engineers. Determination of shear strength parameters comprising of cohesion (c) and internal friction angle (Φ) plays a vital role in soil mechanics. These parameters are often used in quantification of soil strength and thereby play an important role in designing the foundation. In this study, direct shear tests and triaxial tests have been conducted to investigate the shear strength parameters of alluvial soil. Four soil samples were collected from four distinct locations (Rupsha-22˚47’58.01” N, 89˚34’45.82” E; Boyra-22˚50’30.33” N, 89˚32’.63” E; Sonadanga-22˚49’7”.00” N, 89˚32’47.07” E; Fulbarigate 22˚53’56.90” N89˚32’47.07” E) of Khulna. Test results show a significant change in the value of the internal friction angle of the soil samples while its shear strength parameter is measured by a direct shear test compared to triaxial testing on the undisturbed specimen. Whereas, the discrepancy of results is less significant for samples in remoulded conditions. The disparity of shear strength results obtained by different test methods has been explained by analyzing soil sample structure at different states.